Hydrogeochemical Characteristics and Water–Rock Interactions of Coalbed-Produced Water Derived from the Dafosi Biogenic Gas Field in the Southern Margin of Ordos Basin, China - Yuan Bao; Chao An; Chaoyong Wang; Chen Guo; Wenbo Wang (Geofluids)
The hydrogeochemical characteristics of coalbed-produced water can provide insights into the sources of ions and water, the groundwater environments, hydrodynamic conditions, and water-rock interactions of depositional basins. To study the water-rock reaction process and reveal whether there is a microbial activity in the groundwater, a case of the Dafosi biogenic gas field was chosen by testing the ionic concentrations and hydrogen and oxygen isotopic compositions of coalbed-produced water and employing R-type cluster and principal component analyses. The results showed that Na+, Cl−, and HCO3- are the principal ions in the coalbed-produced water, while the water type is mainly a Na–Cl. Due to the hydrolysis of HCO3-, the pH in this region was controlled primarily by HCO3-. As the main cation in water, Na+ contributed substantially to the total dissolved solids. Na+ is also related to the exchange between rock-bound Na+ and Ca2+ and Mg2+ in water or surrounding rocks. The coalbed-produced water’s oxygen isotopes displayed a characteristic 18O drift and enrichment, indicating that the 16O isotope in the water was preferentially exchanged with the coal organic matter. Early evaporation is also contributed to the enrichment of TDS (total dissolved solids) and 18O in the water. The central part of the study area, including the Qijia anticline, was affected by the Yanshanian uplift and denudation and subsequently developed a water-conducting fissure zone and was recharged atmospheric precipitation; these conditions were conducive to the formation of secondary biogenic gas.